Comparison of two methodologies for spectra analysis in coincidence neutron activation analysis - Iberê Souza Ribeiro Jr; Frederico Antonio Genezini; Guilherme Soares Zahn (Brazilian Journal of Radiation Sciences)
The Research Reactor Center (CERPq) of IPEN-CNEN/SP has been developing a facility for Coincidence Neutron Activation Analysis (CNAA), a variation of the Neutron Activation Analysis technique in which gamma-gamma coincidence is used to reduce spectral interferences and improve detection limits of some elements. As the acquisition results in 2D-coincidence spectra, the spectrum analysis has to be dealt with accordingly. There are two distinct ways to perform these analyses, either directly, by fitting bidimensional peaks in the coincidence matrix, or by gating the spectra in one detector around each peak of interest and fitting the resulting 1D-spectrum in the usual way. In this work, the concentrations of As, Co, Cs, Sb and Se were determined in geological and biological reference materials by CNAA using two different methodologies of analysis, using the BIDIM software, which provides 2D-peak-fitting; and a combination of the AnalisaCAEN suite, which gates the 2D-spectra, with Canberra’s Genie2000, which fits the resulting unidimensional spectra. The outcomes allow for a discussion of the advantages and shortcomings of each method, both in terms of usability and of the reliability of the results.